Optimisasi Pengendalian Persedian Alat Tulis Kantor Menggunakan Metode Min-Max Stock pada BPKP Provinsi Sumatera Utara - Aisyah, Siti; Aprianingsih, Melinda; Mutiara, Tia; Filia Sari, Rina; Syuhada Syuhada (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
The use of office stationery (ATK) plays an important role in supporting the smooth operation and administrative activities of government agencies, particularly the Financial and Development Supervisory Agency (BPKP). As an institution whose primary function is to supervise and evaluate state financial management, BPKP requires adequate logistical support to ensure optimal implementation of its duties. One form of such support is the availability of sufficient, timely, and appropriate ATK. Common problems often encountered in ATK management are overstock, which is excess inventory that leads to wasted budget and storage space, and stockout, which is a shortage of inventory that can hinder work activities. This study aims to control ATK inventory by applying the Min-Max Stock method. This method helps in determining the minimum and maximum inventory limits for each type of ATK, so that procurement of goods can be carried out in a planned and efficient manner. With this approach, agencies can maintain a balance between availability of goods and efficient use of the budget. The results of the study indicate that the application of the Min-Max Stock method in the BPKP environment produces more rational inventory figures. For the type of HVS paper F4 size ATK, the minimum and maximum values are set at 12 reams. Meanwhile, for A4-sized HVS paper, the minimum and maximum values are 72 reams and 98 reams, respectively. For printer ink, the ideal minimum and maximum quantities are 74 and 92 bottles. Meanwhile, BPKP logo folders have a minimum value of 240 sheets and a maximum of 325 sheets. The implementation of this method has a positive impact on the efficiency of the procurement and control process of stationery at BPKP.